Burned Bridge how East and West Germans made the Iron Curtain - Sheffer, Edith (Oxford Univ. Press, 2011)
Foundations : Burned Bridge -- Insecurity : border mayhem -- Inequality : economic divides -- Kickoff : political skirmishing -- Shock : border closure and deportation -- Shift : everyday boundaries -- Surveillance : individual controls -- Home : life in the prohibited zone -- Fault line : life in the fortifications -- Disconnect : East-West relations -- Epilogue : new divides